Anti-nociceptive effect of atomoxetine on paclitaxel-induced neuropathic pain in mice and role of alpha-2 adrenergic receptor - Azam Mesdaghinia (Fiyz̤, 2022)
Background: Neuropathic pain due to chemotherapy is one of the most important types of chronic pain that despite the increasing advances in medical sciences, its treatment is associated with many problems. In this study, the effects of atomoxetine on paclitaxel- induced neuropathic pain and the effect of alpha-2 adrenergic receptor antagonist (yohimbine) on the analgesic effect of atomoxetine were investigated. Materials and Methods: Male mice received paclitaxel (2 mg/kg i.p.) from the first to the fifth day and atomoxetine (5, 10, and 15 mg/kg p.o.) was administered from the day 6 to 10. Mice were divided into different groups (n=8) and each group received a unique dose of the drug. On days 9, 10 and 11, Von Frey and acetone tests were performed. Also, the effect of alpha-2 adrenergic receptor antagonist (yohimbine) on the analgesic effect of atomoxetine was investigated. For this purpose, after pain induction, mice received atomoxetine (15 mg/kg p.o) with yohimbine (5 mg/kg i.p. 5) from day 6 to 10. Results: Daily administration of atomoxetine (15 mg/kg p.o) effectively increased pain threshold in the cold and mechanical allodynia tests (P<0.01). Administration a single dose of atomoxetine on the 11th day did not alter behavioral tests. Conclusion: According to these findings, it can be concluded that atomoxetine is able to reduce the severity of paclitaxel-induced neuropathic pain.